PENGARUH KONSEP DIRI TERHADAP PENYESUAIAN DIRI ANAK ASUH DI PANTI ASUHAN AISYIYAH KOTA PADANG - Desi Syafriani (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
Humans or individuals are social creatures where in their daily life they will interact with one another. Interaction can run well if individuals can adjust to other people and their environment. As for what can affect individual self-adjustment is self-concept, self-concept is a way of looking, describing and feeling, thoughts and beliefs about something that people have about themselves, it consists of self-appearance, attitudes, needs, abilities, feelings , character and purpose of life. If the individual has a positive self-concept then the individual's self-adjustment is also positive, and vice versa if the individual has a negative self-concept then the individual's self-adjustment is also negative. This study aims to see how much influence the self-concept has on the child's adjustment at the Aisyiyah Orphanage, Padang. This research is a correlational quantitative research. The population is 35 children in foster care at an orphanage. The sample used is "total sampling" which means that all foster children are used as research samples. This study used a questionnaire to express the self-concept and self-adjustment of foster children, the analysis used is Simple Regression. Based on data analysis, it is known that tcount is 2,047 at the level of significant 0.000, while ttable is 1.68, so tcount >ttable, then Ha is accepted, meaning that the regression coefficient is significant .It can be concluded that there is an effect of self-concept on self-adjustment of foster children at the Aisyiah Orphanage, Padang City.